Study on stirling engine and its associated oscillating flow - Chin, Chau Lung (2016)
Stirling engine is a device which works on the principle of cyclic compression and expansion of a working fluid at different temperatures to generate work. In particular, thermal-lag configuration, a configuration of Stirling engine which only has a moving part consisting of a piston at the end of the cylinder has spark great interest due to its simplicity. This study focus on modification of an existing thermal-lag pulse-tube Stirling engine. Several configurations were studied and the work output were being recorded and discussed. Experiments were done at temperature differences between 245.60c to 330.60c. Experiments showed that increasing the hydraulic radius, rh from 0.1805mm to 1.24mm increases the work output from 0.2cm to 1.097cm. Also, a sharper temperature gradient between the heat exchangers will help bring about higher work output for the test engine. As this type of system works based on oscillating flow, further study on oscillating flow characteristics in a standing-wave acoustic field was being looked into. As such, an experimental setup for a standing-wave acoustic tube for measurement using the particle image velocimetry(PIV) technique was being designed. Numerical simulations were done prior to the fabrication of the setup to understand the oscillating flow characteristics within such a tube. From the simulations, pressure and velocity contours together with variation with time are being studied and discussed. Future study can look into validating the simulations with the PIV measurements of the designed experimental setup. Effective ways of improving output of the pulse tube Stirling engine can be combined and further analyzed. The resonant frequency of such configuration can also be looked into and further optimized to improve performance.